2011
DOI: 10.1007/s12032-011-9918-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic study of derivative chromosome 9 deletion in chronic myeloid leukemia patients

Abstract: The aims of this study are to investigate the frequency of derivative chromosome 9 (der (9)) deletion in Tunisian patients with chronic myeloid leukemia (CML) and to assess the correlation between this deletion and the cytogenetic response for patients treated with hydroxyurea (HU) or imatinib (IM). Karyotype analysis of 336 patients with CML was performed with R-banding technique. Fluorescence in situ hybridization (FISH) was carried using home-brew probes 17L7 and 248J22 for detecting, respectively, adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In patients presenting deletion, we have defined only a single population of 3 BCR and/or 5 ABL deletions, there was not a combination of cells with and without deletions. Thus, suggests that deletion on der(9) chromosome appears at the same time as the translocation t(9;22) and does not constitute a clonal evolution, signing a progression of the disease as reported in some studies (Bennour et al, 2012b;Xinh et al, 2006). Sinclair et al (Albano et al, 2007) reported that deletion breakpoints are various.…”
Section: Deletions On the Derivative Chromosomementioning
confidence: 79%
“…In patients presenting deletion, we have defined only a single population of 3 BCR and/or 5 ABL deletions, there was not a combination of cells with and without deletions. Thus, suggests that deletion on der(9) chromosome appears at the same time as the translocation t(9;22) and does not constitute a clonal evolution, signing a progression of the disease as reported in some studies (Bennour et al, 2012b;Xinh et al, 2006). Sinclair et al (Albano et al, 2007) reported that deletion breakpoints are various.…”
Section: Deletions On the Derivative Chromosomementioning
confidence: 79%
“…The low false positive rate of D‐FISH is achieved by a more complex positive signal pattern, which is characterized by two fusion signals, while there is only one fusion signal in S‐FISH . Nevertheless, Dewald and Vaz reported 9–33% of patients with chronic myeloid leukemia have der(9q) deletion. Deletion of der(9q) leads to the loss of one of two fusion signals in D‐FISH, the same characteristic in S‐FISH with high false positive rate.…”
mentioning
confidence: 99%